Construcción de un análisis técnico del banco de reactores en el Centro de Procesos e Innovación para la Industria Sostenible CEPIIS de la Universidad de América (2025)
At the University of America, the Center for Sustainable Industry (CEPIIS) has a reactor bank acquired by Process Solutions and Equipment (PSE SAS). This equipment was delivered together with its respective operation manual, which includes information on key aspects for its safe handling, such as the generalities of the process, the description of the equipment, technical specifications, installation and operation requirements, important precautions, unit operation and chemical compatibility.